Case Report: Human Umbilical Cord Mesenchymal Stem Cells as a Therapeutic Intervention for a Critically Ill COVID-19 Patient - Zhang, Quan; Huang, Kang; Lv, Jianlei; Fang, Xiang; He, Jun; Lv, Ailian; Sun, Xuan; Cheng, Lamei; Zhong, Yanjun; Wu, Shangjie; Dai, Yao (Frontiers in Medicine, 2021)
Here we report a critically ill patient who was cured of SARS-CoV-2 infection in Changsha, China. A 66-year-old Chinese woman, with no significant past medical history, developed severe pneumonia-like symptoms and later diagnosed as severe COVID-19 pneumonia. Within two months of hospitalization, the patient deteriorated to ARDS including pulmonary edema and SIRS with septic shock. When treatment schemes such as antibiotics plus corticosteroids showed diminished therapeutic value, hUCMSCs therapy was compassionately prescribed under the patient’s consent of participation. After treatment, there were significant improvement in disease inflammation-related indicators such as IL-4, IL-6 and IL-10. Eventually, it confirmed the therapeutic value that hUCMSCs could dampen the cytokine storm in the critically ill COVID-19 patient and modulated the NK cells. In the continued hUCMSCs treatment, gratifying results were achieved in the follow-up of the patient. The data we acquired anticipates a significant therapeutic value of MSCs treatment in severe and critically ill patients with COVID-19, while further studies are needed.